(untitled) (Jurnal Psikologi Udayana, 2015)
Students in their lectures faced on academic and non academic challenge. In academic challenge, such as orientation period, lecture, assignment, mid test, final test, community service and thesis. From non academic challenge, student who join in organization student should be smart to divide their time in campus. Facing the academic and non academic challenge, student must to have toughness in him self to be able face and resolve their lecture as well, student must to have self efficacy. Self efficacy is a judgment one’s ability to organize and execute tasks aims to produce an achievement. Self efficacy can be enchanced through training program, one’s of outdoor training program can be called Outbound. Outbound defined by learning process by interacting through experienced, Outbound is simulation of game in outdoors and have goal to get experience has meaning. This is quantitave research with analysis Paired Sample T-Test. Data collection by use experiment method, pre-experiment design. Researcher deploy self efficacy pre-test scale and self efficacy post-test scale as many as 20 item, data collection techniques use multistage random sampling. Respondent in this research is student in Udayana University, as many as 30 respondent. Result from this research found probability 0,000 (p)<0,05. This means there Outbound influence in self efficacy student. In addition from analysis regresion amount of success variable can be predicts an increase of self efficacy post-test variabel. Based on that data can be concluded Outbound give influence to increase student self efficacy. Keyword : Outbound, Self Efficacy, Student, Experiment